Integrative differential expression and gene set enrichment analysis using summary statistics for scRNA-seq studies - Ying Ma (Nature Portfolio, 2020)
Differential expression (DE) and gene set enrichment (GSE) analysis tend to be carried out separately. Here, the authors present iDEA (integrative Differential expression and gene set Enrichment Analysis) for the analysis of scRNAseq data which uses a Baysian approach to jointly model DE and GSE for improved power in both tasks.